Graffito from Dura Europos and the Hybrid Armor in Parthian-Sasanian Iran - Wójcikowski, Robert S. (Anabasis. Studia Classica et Orientalia, 2013)
The graffito from Dura-Europos depicting a heavily armored cavalryman is one of the most important sources used to reconstruct the armament of Iranian cavalry units seen in the middle of the third century A.D. The graffito presents a hybrid cuirass that is composed of mail and lamellas. It was probably originally an Iranian construction. The use of hybrid armor should be connected with the process of the adaptation of mail in the Parthian empire and then adjusting this new type of body armor to the realities of cavalry combat. The new hybrid cuirass served its purpose well. It not only survived the Parthian era but also the Arabic conquest of Sasanian Iran in the middle of the seventh century A.D., which is evidently demonstrated by the fact that it was present in the military equipment of Muslim armies in the 16th and 17th centuries A.D.